A High Performance and Consolidated Piezoelectric Energy Harvester Based on 1D/2D Hybrid Zinc Oxide Nanostructures. Issue 23 (16th October 2018) - Mahmud, Alam; Khan, Asif Abdullah; Voss, Peter; Das, Taylan; Abdel‐Rahman, Eihab; Ban, Dayan
Abstract: Piezoelectric nanogenerators (PENGs) have manifested their ability over the last decade to deliver sustainable electric power to nano and micro‐electromechanical systems or to make a wireless system network self‐powered by harvesting ambient tiny mechanical energy. Most of the advanced PENGs are based on 1D zinc oxide (ZnO) nanostructures (e.g., nanowires and nanorods) due to their high electromechanical coupling behavior. However, 2D ZnO nanosheets due to their buckling behavior and formation of a self‐formed anionic nanoclay layer contribute to generate direct current type piezoelectric output. Herein, a PENG based on the integration of 1D and 2D ZnO nanostructures on the same substrate is demonstrated for the first time, which is synthesized using a simple, low‐temperature, and low‐cost hydrothermal method. This device has potential to be integrated into the aircraft structural health monitoring (SHM) system to provide required small amount of electrical power to the array of sensors within the system, hence making the SHM system fully wireless. Abstract : A compact and robust piezoelectric nanogenerator (PENG) based on 1D/2D hybrid zinc oxide nanostructures is designed and fabricated with an aim to combine the advantages of PENGs based on ZnO nanowires or nanorods and PENGs based on 2D ZnO nanosheets.